Feasibility of Intracoronary GLP-1 Eluting CellBead™ Infusion in Acute Myocardial Infarction. Issue 3 (March 2013) - Houtgraaf, Jaco H.; De Jong, Renate; Monkhorst, Kim; Tempel, Dennie; Van De Kamp, Esther; Den Dekker, Wijnand K.; Kazemi, Kushan; Hoefer, Imo; Pasterkamp, Gerard; Lewis, Andrew L.; Stratford, Peter W.; Wallrapp, Christine; et al.
Cell therapy is a field of growing interest in the prevention of post acute myocardial infarction (AMI) heart failure. Stem cell retention upon local delivery to the heart, however, is still unsatisfactory. CellBeads were recently developed as a potential solution to this problem. CellBeads are 170-μm alginate microspheres that contain mesenchymal stem cells (MSCs) genetically modified to express glucagon-like peptide-1 (GLP-1) supplementary to inherent paracrine factors. GLP-1 is an incretin hormone that has both antiapoptotic and cardioprotective effects. Transplanting CellBeads in the post-AMI heart might induce cardiomyocyte salvage and ultimately abrogate adverse cardiac remodeling. We aimed to investigate the feasibility of intracoronary infusion of CellBeads in a large animal model of AMI. Four pigs were used in a pilot study to assess the maximal safe dose of CellBeads. In the remaining 21 animals, an AMI was induced by balloon occlusion of the left circumflex coronary artery for 90 min. During reperfusion, 60, 000 CellBeads ( n = 11), control beads ( n = 4), or lactated Ringers' ( n = 6) were infused. Animals were sacrificed after 2 or 7 days, and the hearts were excised for histological analyses. Intracoronary infusion did not permanently affect coronary flow in any of the groups. Histological analysis revealed CellBeads containing viable MSCs up to 7 days. Viability and activity of the MSCs was confirmed by qPCR analysis that showed expression of recombinant GLP-1 and human genes after 2 and 7 days. CellBeads reduced inflammatory infiltration by 29% ( p = 0.001). In addition, they decreased the extent of apoptosis by 25% ( p = 0.001) after 2 days. We show that intracoronary infusion of 5 million encapsulated MSCs is safe and feasible. Also, several parameters indicate that the cells have paracrine effects, suggesting a potential therapeutic benefit of this new approach.